Conversation Training Therapy: Let's Talk It Through - Gartner-Schmidt, Jackie; Gillespie, Amanda I. (Seminars in Speech and Language, 2021)
This article introduces a novel approach to voice therapy called conversation training therapy (CTT). CTT is the first voice therapy approach to remove the therapeutic hierarchy common in most treatment programs. Rather, CTT uses patient-driven conversation as the sole stimuli in therapy to increase perceptual awareness of voice production in conversational speech. The genesis as to why CTT was developed, as well as the conceptual, theoretical, and component parts of CTT, will be explained. In addition, this article will offer examples of the language of therapy, as it applies to CTT and how to trouble-shoot if problems arise. Medical documentation relevant to CTT will also be outlined. Last, results from a recent efficacy study on CTT will be reported.
Keywords: voice therapy; conversation; efficacy; training